2019
DOI: 10.1016/j.intimp.2019.04.037
|View full text |Cite
|
Sign up to set email alerts
|

The A2A receptor agonist CGS 21680 has beneficial and adverse effects on disease development in a humanised mouse model of graft-versus-host disease

Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) is a curative method for blood cancers and other blood disorders, but is limited by the development of graft-versus-host disease (GVHD). GVHD results in inflammatory damage to the host liver, gastrointestinal tract and skin, resulting in high rates of morbidity and mortality in HSCT recipients. Activation of the A 2A receptor has been previously demonstrated to reduce disease in allogeneic mouse models of GVHD. This study aimed to investigate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…This suggests that in addition to reducing GVHD, more frequent dosing with P2X7 antagonists early after transplantation may result in improved donor immune cell engraftment and homeostasis, potentially resulting in a greater protection from opportunistic infections and cancer relapse. In regards to B cell engraftment, previous studies have repeatedly shown absent or negligible B cell engraftment in this humanised mouse model (18,28,42,43) . The action of BBG in promoting B cell engraftment in humanised mice in the current study appeared to be attributed to improved survival of these cells, as BBG prevented the loss of hB cells when cultured with limited amounts of FCS.…”
Section: Discussionmentioning
confidence: 73%
“…This suggests that in addition to reducing GVHD, more frequent dosing with P2X7 antagonists early after transplantation may result in improved donor immune cell engraftment and homeostasis, potentially resulting in a greater protection from opportunistic infections and cancer relapse. In regards to B cell engraftment, previous studies have repeatedly shown absent or negligible B cell engraftment in this humanised mouse model (18,28,42,43) . The action of BBG in promoting B cell engraftment in humanised mice in the current study appeared to be attributed to improved survival of these cells, as BBG prevented the loss of hB cells when cultured with limited amounts of FCS.…”
Section: Discussionmentioning
confidence: 73%
“…PTCy can increase Treg number in allogeneic mouse models of GVHD [54], but there are limited data in humanized mice. We have previously observed human Tregs in humanized NSG mice with GVHD [31,38,49,[55][56][57][58]; however, PTCy is the first treatment in our laboratory to impact these cells in this model. This may validate the impact of PTCy on human Tregs in the current study.…”
Section: Ptcy Reduces Gvhd In a Humanized Mouse Modelmentioning
confidence: 94%
“…Contrary to allogeneic mouse models, injection of caffeine (days 0–14) did not impact weight loss, clinical score, survival, histology or serum cytokine concentrations in a humanised mouse model [ 113 ]. While injection of the A 2A agonist CGS21680 (days −2–11) had confounding effects in these mice, appearing to worsen disease by increasing weight loss and serum human IL-6 concentrations, but also potentially alleviating disease severity by reducing leukocyte infiltration into the liver and serum human TNFα concentrations [ 136 ].…”
Section: Adenosine Receptor Signalling In Gvhdmentioning
confidence: 99%